Áreas verdes e desigualdades sociais em um município de médio porte no Brasil - Ferreira, Cássia Castro Martins (2019)
The study aimed to calculate and spatializing green area index for the city of Juiz de Fora - MG. TheGreen Area Index was calculated based on aerial photographs dating from 2000 and 2007, and thepopulation census of 2000 and 2010, green areas have had little significant changes in their areasduring this period. It has been found a 10.5 IAV m2/hab across the city. The data indicate a reducedgreen area index by urban regions and show the need for a public policy that emphasises the creationof green areas, especially to meet the outlying regions of the city, where occur a higher populationdensity, a lower per capita income and lower green area index. Emphasising that the green areas canprovide for the population better living conditions.